Policy Hybridity in Religious Education: Local Governance and Public Schools Reform - Ardhana Januar Mahardhani; Yazid Fanani; Anip Dwi Saputro; Restu Mufanti (Indonesian Journal of Islamic Education Studies (IJIES), 2025)
This study investigates the rise of hybrid policy dynamics in public education, focusing on the interplay between religious values and administrative logic. This research employs a qualitative case study approach, including document analysis, interviews, and field observations, to explore the policy development process and its implementation at the school level. The results show that the policy emerged from a negotiated process involving government officials, Islamic organizations, and pesantren leaders, resulting in a governance model that integrates moral standards with bureaucratic practices. During its implementation, schools displayed varying degrees of adjustment, shaped by leadership style, teacher skills, and community engagement. At the same time, non-governmental entities significantly contributed as co-governors, influencing the policy's ethical aspects and public legitimacy. Nevertheless, the prominence of major Islamic groups creates worries about inclusivity and equitable representation. The findings of this study indicate that hybrid governance provides a context-specific solution that aligns with local sociocultural norms but requires a more equitable framework to maintain inclusivity and academic integrity, including improved teacher skills, cross-community communication, and assessment methods that incorporate both ethical and educational measures. This study ultimately adds value, both conceptually and practically, by providing an analytical framework for understanding hybrid governance in education and by offering recommendations for crafting policies that embrace religious diversity while fostering inclusivity and superior educational outcomes.